Innovation in public organizations and services: The missing link? A starting point for a transition towards open and collaborative innovation - Ramírez-Alujas, Álvaro V. (Estado, Gobierno y Gestión Pública, 2012)
As well as debating the application and development of the concept ofinnovation in the public sector, the paper proposes an agenda for movingpublic organizations towards a model of collaborative governance withinan open government framework. It is argued that this paradigm shift theconfiguration of public service 2.0 which, understood as open platformsfor collective action, would promote a real and active citizen’s participationand involvement in public management.